Wood ash effects on soil properties and Lactuca sativa growth in soils amended with digestate and poultry litter. (21st April 2023) - Ibeto, Cynthia N.; Lag-Brotons, Alfonso J.; Marshall, Rachel; Semple, Kirk T.
Abstract: The evaluation of the impact of wood ash, on metal uptake and transfer factor of lettuce grown on soil amended with poultry litter, digestate and its fraction was carried out. Positive (inorganic fertilizer) and negative (unamended soil) fertilization controls were included and impacts on soil fertility and crop productivity, as well as potential toxic elements' levels, were assessed at pre and post planting period. Soil properties (e.g., plant available N and P, and water soluble elements), plant morphometry, elemental composition (e.g., total nitrogen, total carbon, total phosphorus) and nutrient uptake were determined using standard methods. There was higher nutritive content of the soil amended with whole digestate than fiber digestate resulting in its largest weight of lettuce. Ash significantly improved the impact of the amendments on the properties of the soil which was reflected in better lettuce productivity and was most applicable to the poultry litter. Based on the transfer factor and uptake of the trace metals, results show lower potential toxicity in the lettuce from the organic treatments in comparison to the inorganic fertilizer. Wood ash had positive ameliorative effects on the amended soils which makes it a suitable nutrient booster for organic fertilizers and alternative to inorganic fertilizers for leafy vegetables.